The acute effect of a plyometric stimulus on jump performance in professional rugby players - Tobin, D. P.; Delahunt, E. (The Journal of Strength and Conditioning Research, 2014)
Post-activation potentiation (PAP) is the elevation of motor performance to a higher level in response to a conditioning stimulus. Extensive research exists examining the PAP effect after a heavy resistance exercise. However, there is limited research examining the PAP effect after a plyometric stimulus. This study was designed to examine whether a plyometric stimulus could produce a PAP effect comparable to that typically reported with a heavy resistance protocol. Importantly, it was hypothesized that the PAP effect would exist without the same levels of acute fatigue resulting from a heavy stimulus, thus allowing improvement in performance within a short rest interval range. Twenty professional rugby players were recruited for the study. Subjects performed 2 countermovement jumps (CMJs) at baseline and at 1, 3, and 5 minutes after a plyometric stimulus consisting of 40 jumps. Two separate 1-way repeated-measures analyses of variance were conducted to compare the dependent variables CMJ height and peak force at the 4 time points. Results of the Bonferroni adjusted pairwise comparisons indicated that jump height and peak force before plyometric exercises were significantly lower than all other time points (p < 0.01). The main finding of this study indicates that a series of plyometric exercises causes a significant acute enhancement in CMJ height (p < 0.01) and peak force (p < 0.01) throughout the rest interval range of 1-5 minutes. The plyometric series induced an improvement in CMJ height comparable to that reported elsewhere after a heavy lifting stimulus but without the need for a prolonged rest interval. Performing repeated series of plyometric jumps appears to be an efficient method of taking advantage of the PAP phenomenon, thus possibly eliminating the need for a complex training protocol.